Production of the antidepressant orcinol glucoside in Yarrowia lipolytica with yields over 6,400-fold higher than plant extraction - Bihuan Chen; Xiaonan Liu; Yina Wang; Jie Bai; Xiangyu Liu; Guisheng Xiang; Wei Liu; Xiaoxi Zhu; Jian Cheng; Lina Lu; Guanghui Zhang; Ge Zhang; et al. (PLoS Biology, 2023)
Orcinol glucoside (OG), mainly found in the rhizome of the traditional Chinese herb Curculigo orchioides Gaertn, is noted for its antidepressant effects. In this study, an efficient screening pipeline was established for identifying the highly active orcinol synthase (ORS) and UDP-dependent glycosyltransferase (UGT) involved in the biosynthesis of OG by combining transcriptome analysis, structure-based virtual screening, and in vitro enzyme activity assays. By enhancing the downstream pathway, metabolic engineering and fermentation optimization, the OG production in Yarrowia lipolytica was improved 100-fold, resulting in a final yield of 43.46 g/L (0.84 g/g DCW), which is almost 6,400-fold higher than the extraction yield from C. orchioides roots. This study provides a reference for rapid identification of functional genes and high-yield production of natural products. This study deciphers the biosynthetic pathway of the antidepressant orcinol glucoside from Curculigo orchioides and engineers the production of orcinol glucoside in Yarrowia lipolytica with yields over 6,400-fold higher than that extracted from its natural plant source.